2018
DOI: 10.1007/s10142-018-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots in the genomic architecture of field drought responses in wheat as breeding targets

Abstract: Wheat can adapt to most agricultural conditions across temperate regions. This success is the result of phenotypic plasticity conferred by a large and complex genome composed of three homoeologous genomes (A, B, and D). Although drought is a major cause of yield and quality loss in wheat, the adaptive mechanisms and gene networks underlying drought responses in the field remain largely unknown. Here, we addressed this by utilizing an interdisciplinary approach involving field water status phenotyping, sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
1
43
1
Order By: Relevance
“…The marker SNP620, located on chromosome 1B and detected in association with SV, was found included into a cluster of 12 genes encoding blue copper proteins (BCP), with homoeologs in the two durum wheat subgenomes (Figure 4, Table 5 and Supplementary Material Figure S6). In the hexaploid wheat genome, this set of genes form a cluster of homeolog triads [72] with a total of 31 genes (Supplementary Materials Table S7 and Figure S7). Additionally, another interesting gene (TraesCS1B01G568400LC.1) was found closer this marker, coding for the ubiquinone biosynthesis O-methyltransferase.…”
Section: Candidate Genes Analysismentioning
confidence: 99%
“…The marker SNP620, located on chromosome 1B and detected in association with SV, was found included into a cluster of 12 genes encoding blue copper proteins (BCP), with homoeologs in the two durum wheat subgenomes (Figure 4, Table 5 and Supplementary Material Figure S6). In the hexaploid wheat genome, this set of genes form a cluster of homeolog triads [72] with a total of 31 genes (Supplementary Materials Table S7 and Figure S7). Additionally, another interesting gene (TraesCS1B01G568400LC.1) was found closer this marker, coding for the ubiquinone biosynthesis O-methyltransferase.…”
Section: Candidate Genes Analysismentioning
confidence: 99%
“…Stomata are typically closed under water-stressed conditions, which reduces crop growth and photosynthesis and may aggravate crop heat stress because of decreased transpirational cooling [8]. The canopy temperature is a good indicator of the response of crops to water stress [315], and scientists have reported that under water stress the measurement can be used to identify drought-adapted cultivars [114], [123], [136], [268], [316]- [318]. Thermal images need to be normalized to the ambient temperature and relative humidity to control the effect of environmental conditions on measurements.…”
Section: Water Stressmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) is widely used to identify stress-related genes, and can also provide key information regarding the expression of genes regulated by transcription factors [40,41]. To explore the genes regulated by ZmBES1/BZR1-5, we performed RNA-seq using the Illumina HiSeq3000 system.…”
Section: Zmbes1/bzr1-5 Regulates the Expression Of Stress-related Genesmentioning
confidence: 99%